Toward operational criteria for ecosystem approaches to health - Richter, C.H.; Steele, J.A.; Hung Nguyen-Viet; Jianchu Xu; Wilcox, B.A. (Springer, 2015)
More than a decade has passed since Forget and Lebel (2001)introduced the ‘‘ecosystem approach to human health’’. Since this first conceptual elaboration, a significant literature has developed describing validity, utility, and general guidelines for a newly emerging research community. Numerous initiatives, many supported by Canada’s International Development Research Center (IDRC), ranging from narrowly focused research studies to large-scale interventions, have focused on health challenges within diverse social-ecological settings. We note that while ‘‘ecohealth’’ was first introduced as a fusion of the ‘‘ecosystem approach to human health’’, inthe following abbreviated as ‘‘ecosystem approach’’, and IDRC’s ‘‘ecohealth program’’, the term is also used in a more generic way. For example, in naming this journal, ecohealth was suggested to broadly include research and practice addressing problems at the interface of the ecological and health sciences (Wilcox et al. 2004; Wilcox et al. 2012).However, ideas of applying the ecosystem concept to human health and that of ‘‘healthy ecosystems’’ have always been at the core of research, dialog and, to our knowledge, most activities and events using the term ecohealth. Other initiatives not directly sponsored by IDRC have also endorsed the idea of ecosystem approaches to health (e.g.PAHO 2009), and applications of the ‘‘one health’’ concept increasingly incorporate an ecosystem perspective (Zinsstag2012). Yet, the operational specifics of the ecosystem approach have been difficult to define, which hampers comparability even among similar interventions, the evaluation of efficacy, and the development of best practices targeting both communal health benefits and procedural efficiencies. We believe more can be done in this regard and present this paper with the following two aims: (1) to derive a set of operational criteria specifically applicable to ecosystem approaches and (2) to offer a protocol derived from our combined experiences and a thorough literature review to suggest an evidence-based best practice technique for the procedural implementation of ecosystem approaches.